Sincronização de microrrede com diferentes fontes de geração distribuída a partir de controle baseado em hierarquia de agentes - Poloni, Patrícia (2020)
The microgrids (MGs) are small-scale electrical power systems that may operate both in islanded and grid-connected modes. The transition between MGs operating modes can result in equipment failures if the operation is performed without attending the required premises and criteria. In particular, the synchronization of MGs, referred to the transition between islanded to grid-connected operation mode, must be performed following the maximum voltage, frequency, and phase angle difference criteria at the Point of Common Coupling (PCC) between MG and the main grid. There are different control strategies to synchronize the MG with the main grid through adjustments in Distributed Generation (DG) sources connected to the MG. In order to determine the impacts of the connection between these systems and evaluate the MG synchronization process, this research focuses on applying a decentralized method based on multi-agent hierarchical control to synchronize a MG which was implemented in Matlab/Simulink R software and has different DG sources on its topology. Furthermore, a synchronization transients analysis routine based on MG simulations was proposed. The hierarchical control starts with the definition and modeling of leaders, followers and synchronism agents under the MG structure and energy sources mode of operation. This research has shown that MG connection influences at the DG sources connected into the MG, especially those based on synchronous generators, even when the connection occurs according to the connection requirements established by literature. The results have established into three scenarios. First it was defined the best agents’ hierarchy for MG synchronization, then evaluated the communication time delay between agents and observed the behavior of the implemented control when load variation occurs. The control method performance was acceptable and has resulted in a MG smooth connection.